2010
DOI: 10.1042/bj20100541
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic roles of the ERK and p38 MAPK signalling pathways in globin expression, haem biosynthesis and iron uptake1

Abstract: Late-stage erythroid cells synthesize large quantities of haemoglobin, a process requiring the co-ordinated regulation of globin and haem synthesis as well as iron uptake. In the present study, we investigated the role of the ERK (extracellular-signal-regulated kinase) and p38 MAPK (mitogen-activated protein kinase) signalling pathways in MEL (mouse erythroleukaemia) cell differentiation. We found that treatment of HMBA (hexamethylene bisacetamide)-induced MEL cells with the ERK pathway inhibitor UO126 results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
(71 reference statements)
1
7
0
1
Order By: Relevance
“…Considering this study, it is of interest to note that blocking the p38 pathway using the inhibitor, SB202190, resulted in reduced total iron uptake in erythroid cells, highlighting the potential significance of this pathway in affecting iron metabolism (63). Indeed, the alterations in p38 phosphorylation observed in this study after manipulation of cellular iron status indicate that this signaling pathway has potential roles in regulating molecules involved in iron metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…Considering this study, it is of interest to note that blocking the p38 pathway using the inhibitor, SB202190, resulted in reduced total iron uptake in erythroid cells, highlighting the potential significance of this pathway in affecting iron metabolism (63). Indeed, the alterations in p38 phosphorylation observed in this study after manipulation of cellular iron status indicate that this signaling pathway has potential roles in regulating molecules involved in iron metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…Our results suggest that phagocytic stimulation by MSU required ERK activation but not p38, which seems to act as a repressor of MSU phagocytosis by OBs. Such antagonistic roles of ERK1/2 and p38 MAPK are reminiscent of another condition in which ERK1/2 and p38 MAPK differentially regulate heme biosynthesis [88]. …”
Section: Discussionmentioning
confidence: 99%
“…Binding of prorenin/renin to (P)RR stimulates the intracellular signaling including ERK1/2 (Liu et al 2011;Nguyen 2011). Mardini et al (2010) showed that the ERK pathway inhibitor U0126 increased intracellular heme and hemoglobin levels, as well as ALAS2 mRNA expression levels, in Friendvirus-infected MEL (mouse erythroleukemia) cells. The ERK1/2 activation by the (P)RR-mediated signaling may be silenced by (P)RR-specific siRNA, resulting in elevated expression levels of ALAS2 mRNA in the present study.…”
Section: Discussionmentioning
confidence: 99%